(3QSGdI aj GdPH Yf ef JGH ef GdPfH WdHkG deQVGJ GdQHs
(3ChdgG (B:s
(3hHYO gPg QSGdI ai GdPH Yf ef JGH ef GdPfH WdHkG deQVGJ GdQH s
(3BNQgG (B:s
(3hdG jcdfG Edi CfaSfG WQaI Yjf Ch Edi CMO ef Ndbg HMeO Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HChdg aGFOIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJUha hGdBOGH GdTQYjIs